2009
DOI: 10.3390/medicina45020012
|View full text |Cite
|
Sign up to set email alerts
|

Associations of emotional state and quality of life with lipid concentration, duration of the disease, and the way of treating the disease in persons with type 2 diabetes mellitus

Abstract: The aim of the study was to evaluate associations of emotional state and quality of life with lipid concentration, duration of the disease, and the way of treating the disease in males and females with type 2 diabetes mellitus. A total of 53 persons with type 2 diabetes mellitus (27 males and 26 females; mean age, 58.7±8.9 years) and 56 healthy persons (26 males and 30 females; mean age, 54.7±8.3 years) participated in the study. Emotional state was evaluated by means of Profile of Mood State and quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
2
Order By: Relevance
“…A similar finding was reported in the USA, ie, after multivariable analysis, DRD was associated only with HbA 1c and not with BP or LDL-C. 47 However, in a study from Lithuania, significant correlations were found between scores for emotional state (tension-anxiety, depression-dejection, and confusion-bewilderment) and lipid levels (total cholesterol, triglycerides, and low-density lipoprotein cholesterol) in patients with T2D, especially women. 48 It is less clear whether there is any physiological link between DRD or DS and lipid metabolism compared to that is known between these emotional distress with glucose and BP. 12 , 49 Hence, DRD or DS might influence disease control through changed self-care activity 50 and health behavior, such as dietary choices, physical exercise, and adherence with therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported in the USA, ie, after multivariable analysis, DRD was associated only with HbA 1c and not with BP or LDL-C. 47 However, in a study from Lithuania, significant correlations were found between scores for emotional state (tension-anxiety, depression-dejection, and confusion-bewilderment) and lipid levels (total cholesterol, triglycerides, and low-density lipoprotein cholesterol) in patients with T2D, especially women. 48 It is less clear whether there is any physiological link between DRD or DS and lipid metabolism compared to that is known between these emotional distress with glucose and BP. 12 , 49 Hence, DRD or DS might influence disease control through changed self-care activity 50 and health behavior, such as dietary choices, physical exercise, and adherence with therapy.…”
Section: Discussionmentioning
confidence: 99%
“…High lipid levels in women are correlated with total score values for emotional state characteristics (i.e. tension, anxiety, depression, dejection, and confusion) [16] . Personality traits are important because they include emotion, thought, and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A study on diabetic men found that questionnaire‐based vigour‐activity correlated with total cholesterol level and inversely correlated with triglyceride levels (Lasaite et al . ). Therefore, another major aim in this study was to examine associations of cardiovascular risk factors (blood glucose, blood lipids, BMI) with vitality score.…”
mentioning
confidence: 97%